Le mouvement de réforme municipale, 1880-1920 - Caron, Christine (CRDP, 1979)
Keywords: Réformistes

The Municipal Reform Movement in Montreal, 1886-1914 - Gauvin, Michel (Université d'Ottawa, 1972)
Keywords: Réformistes

Tomorrow's Metropolis: The Urban Reform Movement in Canada, 1880-1920 - Rutherford, Paul (The Canadian City: Essays in Urban and Social History, 1984)
Keywords: Réformistes

Tomorrow's Metropolis: The Urban Reform Movement in Canada, 1880-1920 - Rutherford, Paul (SHC / CHA, Historical Papers / Communications historiques, 1971)
Keywords: Réformistes

Les Mouvements de réforme urbaine à Montréal au tournant du siècle. Modes de développement, modes d'urbanisation et transformations de la scène politique - Germain, Annick (Centre d'information et d'aide à la recherche, Département de sociologie, Université de Montréal, 1984)
Keywords: Réformistes

Les mouvements de réforme urbaine à Montréal au tournant du siècle. Modes de développement, modes d'urbanisation et transformations de la scène politique - Germain, Annick (Université de Montréal, 1980)
Keywords: Réformistes

L'émergence d'une scène politique: mouvement ouvrier et mouvements de réforme urbaine à Montréal au tournant du siècle - Essai d'interprétation - Germain, Annick (Revue d'histoire de l'Amérique française, 1983)
Number: 2
Keywords: Réformistes

Ames as Municipal Reformer - Russell, Daniel J. H. B. (Université McGill, 1972)
Keywords: Ames; Herbert Brown; Réformistes

Industrial Efficiency, Social Order and Moral Purity: Housing Reform Thought in English Canada, 1900–1950 - Purdy, Sean (Urban History Review / Revue d'histoire urbaine, 1997)
Number: 2
Keywords: Logement; Réformistes

Gentrification and Reform Politics in Montréal, 1982 - Ley, David; Mills, Caroline (Cahiers de géographie du Québec, 1986)
Number: 81
Keywords: Gentrification; Réformistes; Élections

Georges-Émile Lapalme: un réformiste engagé, 1930-1960 - Panneton, Jean-Charles (Université du Québec à Montréal, 1999)
Keywords: Lapalme; Georges-Émile; Réformistes

A Not Unreasonable Claim. Women and Reform in Canada 1880s - 1920s - Kealey, Linda (Women's Educational Press, 1979)
Keywords: Femmes; Féminisme; Réformistes

Le mouvement des réformes sociales et la marginalisation des prostituées à Montréal - Lévesque, André (Résistance et transgression. Études en histoire des femmes au Québec, 1995)
Keywords: Femmes; Prostitution; Réformistes

Le mouvement des réformes sociales et la marginalisation des prostituées à Montréal - Lévesque, André (Normes et marginalités. Comportements féminins aux XIXe et XXe siècles. Actes du colloque tenu à l'Université Libre de Bruxelles, les 11-12 mai 1990, 1991)
Keywords: Femmes; Prostitution; Réformistes

Éteindre le Red Light: les réformateurs et la prostitution à Montréal, 1865-1925 - Lévesque, Andrée (Urban History Review / Revue d'histoire urbaine, 1989)
Number: 3
Keywords: Femmes; Prostitution; Réformistes

La tuberculose à Montréal au début du XXe siècle: problème social et réponse réformiste - Pierre-Deschenes, Claudine (Université du Québec à Montréal, 1980)
Keywords: Médecine; Réformistes; Tuberculose

Manliness, Goodness, and God: Poverty, Gender, and Social Reform in English-Speaking Montreal, 1890-1929 - Perry, Ann Kirsten (Université Queen's, 1998)
Keywords: Anglophones; Pauvreté; Réformistes

W.D. Lighthall: Sometime Confederation Poet, Sometime Urban Reformer - Wright, Donald A. (Université McGill, 1991)
Keywords: Lighthall; William Douw; Réformistes; Écrivains

Réformisme et catholicisme: la pensée sociale d'Arthur Saint-Pierre - Dupuis, Jean-Claude (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1991)
issued: 1991-24-00
Keywords: Idéologies; Réformistes; École Sociale Populaire

La politique municipale à Montréal, de 1910 à 1914: l'échec des réformistes et le triomphe de Médéric Martin - Nagant, Francine (Université de Montréal, 1983)
Keywords: Maires; Martin; Médéric; Réformistes

The Reformer and the Machine : Montreal Civic Politics from Raymond Préfontaine to Médéric Martin - Gauvin, Michel (Journal of Canadian Studies / Revue d'études canadiennes, 1978)
issued: 1978-22-00
Keywords: Maires; Martin; Médéric; Préfontaine; Raymond; Réformistes

Practical Idealism: Women in Urban Reform, Julia Drummond and the Montreal Parks and Playgrounds Association - Wolfe, Jeanne M.; Strachan, Grace (Life Space, Gender, Household, Employment, 1988)
Keywords: Drummond; Julia; Montreal Parks and Playgrounds Association; Parcs; Réformistes

L'enseignement et la pratique de l'hygiène dans les écoles primaires catholiques du Québec de 1905 à 1944: un progrès ou un contrôle? - Duquette, Isabelle (Université de Sherbrooke, 1994)
Keywords: Réformistes

Canadian Urban Reformers and Industrialization: the Case of Montreal - O'Neal, Brian (Historical Discourses, 1988)
Keywords: Réformistes

Metropolitan Reform in Montreal - Baril, Paul-André (Université McGill, 1980)
Keywords: Communauté urbaine

The Beginnings of Reform Judaism in Canada - Brown, Michael (Jewish Social Studies, 1972)
Keywords: Emanu-el (temple); Juifs

La communauté urbaine de Montréal: une réforme ratée - Benjamin, J. (L'Aurore, 1975)
Keywords: Communauté urbaine

Reform, Planning, and City Politics: Montreal, Winnipeg, and Toronto - Kaplan, Harold (University of Toronto Press, 1982)

The Language Problem and School Board Reform on the Island of Montréal - Mackay, Murdo (Université McGill, 1987)
Keywords: Langue

Les syndicats internationaux et les réformes scolaires au Québec (1900-1930) - Bastien, Céline (Université de Montréal, 1997)
Keywords: Syndicats internationaux

Pour une école démocratique: Gérard Filion et les réformes scolaires des années 1960 - Jomphe, Carl (Université du Québec à Montréal, 1998)

Sex, Politics and Religion: Controversies in Female Immigration Reform Work in Montreal, 1881-1919 - Roberts, Barbara Ann (Atlantis, 1980)
issued: 1980-23-00
Keywords: Femmes; Protestants

La réforme à la ville de Montréal: une expérience de gestion du 3e type? - Laliberté, Marie-France (Université Laval, 1990)

Rapports de pouvoir et émergence d'une nouvelle élite canadienne-française à Montréal, 1880-1914 - Linteau, Paul-André (Études canadiennes / Canadian Studies, 1986)
Number: 1
Keywords: Bourgeoisie; Réformistes

Ward Heelers and Honest Men: Urban Québécois Political Culture and the Montreal Reform of 1909 - Gordon, Alan (Urban History Review / Revue d'histoire urbaine, 1995)
Number: 2
Keywords: Canada (Le); Libéralisme; Patrie (La); Presse (La)

La Fédération des Écoles Normales: Analyse de ses stratégies au moment de la réforme scolaire 1964-1969 - Boisvert, Dominic (Université de Sherbrooke, 1998)
Keywords: Fédération des écoles normales; Écoles normales

To Correct their Faults and Reform their Souls: A Portrait of Two Quebec Reformatory Schools, 1873-1924 - Martyn, Peter Howard (Université Concordia, 1986)
Keywords: Délinquance; Enfants

Ville et prison: discours d'hygiénistes réformateurs à Montréal au cours de la deuxième moitié du XIXe siècle - Dufresne, Martin (Criminologie, 1995)
Number: 2
Keywords: Médecine; Prisons; Épidémies

Une politique de l'enfance délinquante: la mise en place de l'école de réforme des garçons de Montréal, 1850-1873 - Ménard, Sylvie (Bulletin d'histoire politique, 1998)
issued: 1998-24-00
Keywords: Bourget; Ignace; Délinquance; Enfants; Ultramontains; Évêques

Une bureaucratie en voie de formation: l’administration municipale de Montréal dans la première moitié du XXe siècle - Dagenais, Michèle (Revue d'histoire de l'Amérique française, 1992)
Number: 1
Keywords: Fonctionnaires; Hôtel de ville; Réformistes

Dynamique d'une bureaucratie. L'administration municipale de Montréal et les fonctionnaires, 1900-1945 - Dagenais, Michèle (Université du Québec à Montréal, 1992)
Keywords: Fonctionnaires; Hôtel de ville; Réformistes

The Politics of Progressivism in Quebec: the Gouin 'Coup' Revisited - Dutil, P. A. (Canadian Historical Review, 1988)
Number: 4
Keywords: Montreal Light; Heat and Power; Réformistes

Dynamiques d'une bureaucratie: l'administration municipale de Montréal et ses fonctionnaires: 1900-1945 - Dagenais, Michèle (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1993)
issued: 1993-22-00
Keywords: Fonctionnaires; Hôtel de ville; Réformistes

Echoing in the Silence of Redemption: Discourses of Nationhood and Identity in Quebec - Gagnon, Michelle (Université Concordia, 1994)
Keywords: Nationalisme; Plante; Pacifique (Plante; Pax); Réformistes; Télévision

The Fédération Nationale St-Jean-Baptiste and the Women's Movement in Quebec - Lavigne, Marie; Pinard, Yolande; Stoddart, Jennifer (A Not Unreasonable Claim. Women and Reform in Canada 1880s-1920s, 1979)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Féminisme

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires